Intravenous immunoglobulin is safe and effective in controlling pre-existing paraneoplastic neuromuscular diseases in cancer patients treated with immune checkpoint inhibitors: two case reports and literature review - Xiong, Ge; Young, Richard Benjamin; Chow, Helen; Maverakis, Emanual; Maselli, Ricardo A.; Richman, David Paul; Li, Tianhong (Frontiers in Oncology, 2023)
Immune checkpoint inhibitors cause rare but potentially fatal neuromuscular complications, leading to a concern to use these agents in cancer patients with pre-existing autoimmune or inflammatory neuromuscular diseases. We report two such patients with paraneoplastic dermatomyositis and “seronegative” paraneoplastic demyelinating neuropathy, respectively, who have been successfully treated with immune checkpoint inhibitor monotherapy as well as maintenance intravenous immunoglobulin. While controlling the paraneoplastic or autoimmune neuromuscular diseases, the use of intravenous immunoglobulin did not compromise the anti-cancer effect of immune checkpoint inhibitor.